Physician behaviour for antimicrobial prescribing for paediatric upper respiratory tract infections: a survey in general practice in Trinidad, West Indies - Ramdhanie Joseph; Parmasad Vishala; Mathur Deepti; Dindial Ria; Dharamraj Kavita; Mohan Shaun; Matthew Jason; Pinto Pereira Lexley M (BMC, 2004)
Abstract Background Upper respiratory tract infections (URTIs) are among the most frequent reasons for physician office visits in paediatrics. Despite their predominant viral aetiology, URTIs continue to be treated with antimicrobials. We explored general practitioners' (GPs) prescribing behaviour for antimicrobials in children (≤ 16 years) with URTIs in Trinidad, using the guidelines from the Centers for Disease Control and Prevention (CDC) as a reference. Methods A cross-sectional study was conducted on 92 consenting GPs from the 109 contacted in Central and East Trinidad, between January to June 2003. Using a pilot-tested questionnaire, GPs identified the 5 most frequent URTIs they see in office and reported on their antimicrobial prescribing practices for these URTIs to trained research students. Results The 5 most frequent URTIs presenting in children in general practice, are the common cold, pharyngitis, tonsillitis, sinusitis and acute otitis media (AOM) in rank order. GPs prescribe at least 25 different antibiotics for these URTIs with significant associations for amoxicillin, co-amoxiclav, cefaclor, cefuroxime, erythromycin, clarithromycin and azithromycin (p < 0.001). Amoxicillin alone or with clavulanate was the most frequently prescribed antibiotic for all URTIs. Prescribing variations from the CDC recommendations were observed for all URTIs except for AOM (50%), the most common condition for antibiotics. Doctors practicing for >30 years were more likely to prescribe antibiotics for the common cold (p = 0.014). Severity (95.7%) and duration of illness (82.5%) influenced doctors' prescribing and over prescribing in general practice was attributed to parent demands (75%) and concern for secondary bacterial infections (70%). Physicians do not request laboratory investigations primarily because they are unnecessary (86%) and the waiting time for results is too long (51%). Conclusions Antibiotics are over prescribed for paediatric URTIs in Trinidad and amoxicillin with co-amoxiclav were preferentially prescribed. Except for AOM, GPs' prescribing varied from the CDC guidelines for drug and duration. Physicians recognise antibiotics are overused and consider parents expecting antibiotics and a concern for secondary bacterial infections are prescribing pressures. Guidelines to manage URTIs, ongoing surveillance programs for antibiotic resistance, public health education on non-antibiotic strategies, and postgraduate education for rational pharmacotherapy in general practice would decrease inappropriate antibiotic use in URTIs.